INVESTIGATING INDUSTRY DYNAMICS IN A RECESSIONARY TRANSITION ECONOMY (The South East European Journal of Economics and Business, 2018)
The paper investigates the statistical regularities of industry dynamics in a transition economy and its manufacturing industry over a six-year period of recession. The static analysis of distributions supports several established stylized facts on firm size and growth-rate distributions. The growth rate distribution featured a sequential, year-by-year procyclical change of the left side of distribution, suggesting that the more years an economy spends in a recession, the greater the decline in the revenue of its firms. On the “growing” side, the recession opened increasing growth opportunities for a small subset of small firms, while it diminished growth opportunities for medium and large firms. The segregation of sectors by technological intensity gives evidence that the high-tech sectors show upward trend of the growth rate distributions’ right side of as the recession unfolded. Sectorial concentration ratios mostly increased, while changes in the unimodality of the firm-size distribution occurred at the end of the economic downturn.